2019
DOI: 10.1021/acs.jpcc.9b03223
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Phase Transitions in Superlattice Assemblies of Cuboidal CH3NH3PbI3 Nanocrystals Followed by Grazing Incidence X-ray Scattering

Abstract: Colloidal nanocrystals of CH 3 NH 3 PbI 3 (MAPI) with the tetragonal crystal structure and cuboidal shape terminated by {110} and {002} facets were assembled into superlattices with cubatic structure and heated under nitrogen while collecting in situ grazing incidence small-and wide-angle Xray scattering (GISAXS and GIWAXS). The nanocrystals have completed a tetragonal-to-cubic phase transition by 60 °C similar to bulk films. GISAXS shows that the superlattice remains stable until 90 °C. At this temperature, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 72 publications
(100 reference statements)
0
39
0
Order By: Relevance
“…In comparison to the many studies on inorganic perovskite NCs, organic–inorganic hybrid perovskite nanocubes have been rarely reported. , In 2016, Vybornyi et al . demonstrated a polar-solvent-free colloidal synthesis of MAPbBr 3 perovskite NCs by the HI method.…”
Section: Shape-controlled Synthesis Of Mhp Ncsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to the many studies on inorganic perovskite NCs, organic–inorganic hybrid perovskite nanocubes have been rarely reported. , In 2016, Vybornyi et al . demonstrated a polar-solvent-free colloidal synthesis of MAPbBr 3 perovskite NCs by the HI method.…”
Section: Shape-controlled Synthesis Of Mhp Ncsmentioning
confidence: 99%
“…They were able to tune the morphology from nanocubes to nanoplatelets and nanowires by varying the reaction parameters. In 2019, Zhang et al extended this method to the synthesis of monodisperse MAPbI 3 nanocubes . The main problem associated with these MA-based perovskites is their chemical decomposition, which limits their applications.…”
Section: Shape-controlled Synthesis Of Mhp Ncsmentioning
confidence: 99%
“…[41,44,49,50] Further lowering the symmetry, the tetragonal I4/mcm phase undergoes a first-order transition into a orthorhombic Pnma phase at 160 K. [41,43,[51][52][53] The temperaturedependent lattice parameters are depicted in Figure 4 (a), indicating the three different phases and the respective phase transition temperatures. The transition between the tetragonal and cubic phase takes place at temperatures around 330 K, [12,[42][43][44]48,50,54] with transition temperatures reported as low as 327 K [42,48] and as high as 331 K, [50] corresponding to the appearance/ disappearance of the tetragonal (211) reflection. Pinpointing the temperature has been challenging as it has been found to depend on the direction of the transition [43,52] and at least the low temperature transition from tetragonal to orthorhombic was shown to depend on the crystal size as Stavrakas et al reported recently.…”
Section: Phase Transitionsmentioning
confidence: 99%
“…Regardless of the synthetic methods and surface passivations of CsPbX3 nanocrystal building blocks, their dynamic chemistry makes nanocrystal assemblies metastable, as has been documented in reports of coalescence and halide expulsion under external stimuli such as pressure, 32 heating [33][34][35] or illumination. 36 Much less is known about the nanocrystal stability in superlattices under common sample handling conditions (e.g., under vacuum or in the air) and its effect on the optical properties of individual superlattices.…”
Section: Introductionmentioning
confidence: 99%